Manfaat chatGPT dalam hubungan manusia dengan alam: menggunakan chatGPT di bidang pertanian - Basuki, Ridwan; Martin, Laila; Mulyani, Nurul (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2023)
ChatGPT, a powerful language model, claims to be able to analyze data and provide actionable agricultural insights. According to him, this data can be used for crop forecasting, soil analysis, plant disease and pest identification, precision farming and irrigation scheduling. ChatGPT states that it can be used to generate accurate and timely reports, alerts, and insights that can help businesses make more informed decisions, improve results, and improve customer service. In this article the author explores the potential use of GPT chat in agriculture, according to him. The author admits asking chatGPT questions about its uses for agriculture. Some of its stated uses are possible now and some are potential for the future. The author has analyzed and edited GPT chat replies.